IMPLIKASI PEMBERLAKUAN UNDANG-UNDANG NO. 28 TAHUN 2009 TENTANG PAJAK DAN RETRIBUSI DAERAH (STUDI PADA PEMERINTAH KABUPATEN TULUNGAGUNG) - Ngazizah, Siti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research purposes to know how the validity of implication law number 28 by the year 2009 and the efforts ofCentral Government in optimizing of its region acceptations. The result of this research showed that thegovernment of Tulungagung district has adjusted tax rates and local retribution in accordance with law ofregulations as well as arrenged in Territory Regulation number 16 by the year 2010. Transfer of tax acquisitionof land and building (BPHTB) become local tax has been implemented since January 1, 2011 using SIMPDapplications with the 2011 target of Rp 3.872.452.466 realized of Rp. 3.095.510.499, in 2012 amount ofÂ  Rp5.390.360.827realized of Rp. 4.200.000.000 and in 2013 the target of Rp 4.500.000.000, while the transfer ofland and building tax Rural and Urban (PBBP2) be a local tax will be applying on January 1, 2014 with thevarious steps being taken that is, in 2010Â Determination of regulation, in 2011 to form the organizationalstructure and governance work in accordance with the functions of the Directorate General of Taxation, in 2012the procurement of hardware and software application support SISMIOP with three staff assigned to the task oflearning in STAN, in 2013, procurement of forms and means of collecting PBBP2. The readiness of RegencyGovernment of Tulungagung in implementing the application the law PDRD expected can increase the regionalrevenue from the tax sector and regional retribution, the increase will also supported by intensifying efforts. Keywords: Regional Tax, Regional Retribution, and Law number 28 by the year 2009